Otomatisasi Publikasi Resource File Sharing Menggunakan UPnP Based System - Anggi Atmajaya Siagian; Eko Sakti Pramukantoro; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Many technology offer to do the transfer data process. But those technology have its weakneses. UPnP is one of file sharing technology who able to cover the other weakneses. With using ssdp and soap protocol, UPnP able to zero configuration, multicast and can be used with various platform. Research using implementative method to able find out how UPnP can do the transfer data process and its performance in a network. The author do experiment to program model dan modify it so the program accordingly as desired. Program model successfully created and devided into server program and client program. From the program model UPnP able to do data transfer process with help from http protocol. For UPnP performance, with 500Mb data transfer speed can reach 15.69Mbps and with 1Gb data transfer speed can reach 4.65Mbps and from testing, server can accommodate 3 clients.